فاعلية استخدام استراتيجية السرد القصصي في تدريس اللغة العربية على تحسين مهارات فهم المقروء لدى تلميذات الصف الرابع الابتدائي في مدينة الرياض - آل ثنيان، هند بنت عبدالله بن محمد (جامعة الملك خالد - كلية التربية - مركز البحوث التربوية, 2024)
استهدف البحث الكشف عن فاعلية استراتيجية السرد القصصي في تحسين المستويات الأربع لفهم استهدف البحث الكشف عن فاعلية استراتيجية السرد القصصي في تحسين المستويات الأربع لفهم المقروء (الحرفي، والتحليلي الذي يشمل مهارات التفسير والاستنتاج، والنقدي، والإبداعي) لدى تلميذات الصف الرابع الابتدائي. وقد اتبع البحث المنهج شبه التجريبي ذا المجموعتين التجريبية والضابطة، حيث تم اختيار عينة مكونة من (٥٠) تلميذة من تلميذات الصف الرابع الابتدائي، تم تقسيمهن إلى مجموعتين: مجموعة ضابطة ومجموعة تجريبية، ثم طُبق اختبار قبلي في فهم المقروء للتأكد من تكافؤ المجموعتين قبل إخضاع المجموعة التجريبية لتجربة التدريس باستراتيجية السرد القصصي، وبعد ذلك أجري الاختبار نفسه بعديا على المجموعتين بعد الانتهاء من تجربة البحث باستخدام استراتيجية السرد القصصي. وكشفت نتائج البحث عن فاعلية استراتيجية السرد القصصي في تحسين مهارات فهم المقروء؛ حيث بلغ المتوسط الحسابي لدرجات المجموعة الضابطة (٤٩,٢٨)، وبلغ المتوسط الحسابي لدرجات المجموعة التجريبية (۸۹,۹۲) درجة، وقيمة (ت) المحسوبة (٢٢,٩٦٦) بمستوى معنوية (۰,۰۰۰) وهي نتيجة إجمالية تشير إلى وجود فرق ذي دلالة إحصائية بين درجات التلميذات في المجموعة الضابطة، ودرجات التلميذات في المجموعة التجريبية لمصلحة المجموعة التجريبية؛ مما يدل على التحسن الكبير والملحوظ لمستوى تلميذات المجموعة التجريبية التي تم تدريسها باستخدام استراتيجية السرد القصصي. The research aimed at revealing the effectiveness of the Storytelling Strategy in improving Reading Comprehension (Literal Comprehension, Analytical (Interpretation and Conclusion), Critical, and Creativity) in Fourth-Grade students at Elementary School. To achieve this goal, a sample of (50) students from the fourth grade in an Elementary school was selected, and they were divided into two groups: A Control Group and an Experimental Group. Then a Pre-Test in Reading Comprehension was conducted to ensure that the two groups were of similar abilities before subjecting the experimental group to the experience of teaching by using the Storytelling Strategy, and then the same Test was conducted as a Post-Test on both groups as a final step after the completion of the experiment of teaching using the Storytelling Strategy. The results of the research revealed the effectiveness of the Storytelling Strategy in improving Reading Comprehension Skills. The arithmetic average of the control group's scores was (49,28) and the arithmetic average of the experimental group's scores was (89.92) degrees. The Calculated (T) value reached (22.966) with a significant level of (0.000), which indicating the existence of statistically significant differences between the scores of the students in the control group and the students' level in the experimental group, which in turn indicates the significant and noticeable improvement in the students' levels in the experimental group who were subjected to teaching using Storytelling Strategy.
Keywords: العملية التعليمية -- أدب الأطفال -- مهارات القراءة -- المرحلة الابتدائية -- السعودية